Effects and Mechanisms of Acupuncture Combined with Mesenchymal Stem Cell Transplantation on Neural Recovery after Spinal Cord Injury: Progress and Prospects. (25th September 2020) - Tang, Huiling; Guo, Yi; Zhao, Yadan; Wang, Songtao; Wang, Jiaqi; Li, Wei; Qin, Siru; Gong, Yinan; Fan, Wen; Chen, Zelin; Guo, Yongming; Xu, Zhifang; et al.
Abstract : Spinal cord injury (SCI) is a structural event with devastating consequences worldwide. Due to the limited intrinsic regenerative capacity of the spinal cord in adults, the neural restoration after SCI is difficult. Acupuncture is effective for SCI-induced neurologic deficits, and the potential mechanisms responsible for its effects involve neural protection by the inhibition of inflammation, oxidation, and apoptosis. Moreover, acupuncture promotes neural regeneration and axon sprouting by activating multiple cellular signal transduction pathways, such as the Wnt, Notch, and Rho/Rho kinase (ROCK) pathways. Several studies have demonstrated that the efficacy of combining acupuncture with mesenchymal stem cells (MSCs) transplantation is superior to either procedure alone. The advantage of the combined treatment is dependent on the ability of acupuncture to enhance the survival of MSCs, promote their differentiation into neurons, and facilitate targeted migration of MSCs to the spinal cord. Additionally, the differentiation of MSCs into neurons overcomes the problem of the shortage of endogenous neural stem cells (NSCs) in the acupuncture-treated SCI patients. Therefore, the combination of acupuncture and MSCs transplantation could become a novel and effective strategy for the treatment of SCI. Such a possibility needs to be verified by basic and clinical research.